Rates and Correlates of Antiretroviral Therapy Use and Virologic Suppression Among Perinatally and Behaviorally HIV-Infected Youth Linked to Care in the United States. - Kahana, Shoshana Y; Fernandez, Maria Isabel; Wilson, Patrick A; Bauermeister, Jose A; Lee, Sonia; Wilson, Craig M; Hightow-Weidman, Lisa B (Journal of acquired immune deficiency syndromes (1999), 2015)
To measure rates of antiretroviral therapy (ART) use and virologic suppression among perinatally HIV-infected youth (PIY) and behaviorally HIV-infected youth (BIY) linked to care in the United States and examine the effects of demographic, biomedical, and psychosocial factors on those rates.